SPP Program: An effort to prevent Covid-19 in Tenayan Raya District, Pekanbaru Indonesia - Ramlan Darmansyah; Ndaru Idris; Feri Desfri; May Sri Astuti; Nissa Hedayati; Ferby Hidayat Zafitra; Mutiatul Annisa; Nadia Aprilia; Roma Florentina Simatupang; Fenita Wulandari (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2021)
Tenaya Raya district Pekanbaru Indonesia was the second higher rank area of covid-19 spread in Pekanbaru city. We did a Community empowerment program: SPP (Socialization, Prevention, and Data Collection) in Tenayan Raya District. The program's implementation was done for 14 working days, started from June 15 to 30, 2020. The socialization activity aimed to understand the importance of Covid-19 prevention through media such as; brochures and banners in Tenan Raya district. Moreover, the socialization activity also was done by counseling for markets and daily merchants. Then, prevention activities were like disinfectant spraying, masker distribution, hand washing facilities for comfortable and safe activities. In addition, the data collection activity about community medical history was used for policy-making related to Covid-19 prevention. The method that was used in this research was counseling and speech or gave information about Covid-19 to the community. The result was the socialization program, and Covid-19 prevention was done well, which can be perceived as improving the community understanding about Covid-19. It can be seen by community awareness in using masker, washing hand in a public place, for example; market place and disinfectant spraying in worship place twice or three times a week.